Optimizing Digital Literacy for Privacy Security for Teachers and Students at Mizanul Ulum Islamic Boarding School, Sanrobone Village, Takalar Regency - Erick Irawadi Alwi; Jasmaniar (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
This Community Service Program (PKM) aims to improve the digital literacy skills of teachers and students at the Mizanul Ulum Islamic Boarding School in Sanrobone Village, Takalar Regency, with a primary focus on personal data security and privacy protection in the digital space. With the increasing use of digital devices, the internet, and social media in daily learning and communication, teachers and students are increasingly exposed to the risk of cyber threats such as phishing, malware, digital fraud, and identity theft. This situation demonstrates that the ability to understand and implement digital security is not only a necessity but a fundamental competency required in the era of digital transformation.This training was attended by 30 participants, consisting of 15 teachers and 15 students, over three days. The implementation method included a pre-test to determine initial understanding, material delivery through interactive socialization and case studies, group discussions, and a post-test to measure participants' knowledge gains. The training materials covered safe online behavior, how to manage social media privacy and security, creating strong passwords, recognizing types of digital threats, and a basic understanding of the Electronic Information and Transactions Law (UU ITE), the legal framework for technology use in Indonesia.Based on statistical analysis using a paired sample t-test, results showed a significant increase (p < 0.05) in all participants' digital literacy indicators. The highest increases were seen in the ability to manage social media privacy (122.86%) and the ability to create secure passwords (150%). These findings demonstrate that the Islamic boarding school-based digital literacy training program is highly effective in fostering a safe, ethical, and responsible digital culture for both educators and students, thus supporting a more adaptive and secure modern learning process in the digital era.